PENERAPAN MODIFIKASI PERMAINAN LARI ESTAFET UNTUK MENINGKATKAN MOTIVASIÂ SISWA DAN HASIL BELAJAR DALAM PEMBELAJARAN PENJASORKES (STUDI PADA SISWA KELAS VIII SMP NEGERI 2 TEMBELANG JOMBANG) - ZULFASARI, RINA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Education as a process of building and developing a lifelong student and hosted by giving example, the willingness to build and develop creativity in the learning process. Education has a pedagogical objective, therefore less education complete without Penjasorkes, because Penjasorkes as a basis for physical activity to get to know people in the world and himself that naturally evolved in line with the changing times. For that to Penjasorkes learning process can run smoothly and be able to bring a sense of excitement and motivation of students for learning, teachers have to be good at sport to develop various modifications according to the characteristics of the students in the form of modified sports games. Of the learning process is also expected to develop a change in behavior that is reflected by the results of student learning. To know the characteristics of the growth and development of students, teachers should prepare a method that should reflect the characteristics Penjasorkes itself. Modification is one attempt to do by teachers that reflect learning DAP (Development Appropriate Practice). The purpose of this study was to determine the effect of the application of a relay race game modification to increase student motivation and learning outcomes in learning Penjasorkes. The population in this study were eighth grade students of SMP Negeri 2 Tembelang Jombang with samples of class VIII-B totaled 35 students as the experimental group and class VIII-F totaled 35 students as a control group. From this research we can conclude that there is significant application modifications relay games to improve student motivation as evidenced from the results of test 8.093 t count > t table value of 1.664 with significant level 0.05. There is no significant effect of the application of game modifications relay on result learning in learning Penjasorkes as evidenced from the results of test t count 0.78 < t table value 1.664 with significant level 0.05. There is resulting effect the form of a relay race game modification in learning Penjasorkes to improve student motivation as 9.30%. Keywords: Modified, Motivation, Results Learning of Relay Race